Răspuns :
3x² =27
x²=9
x=+/- 3
7x²=64/7
x²=64/49
x=+/- 8/7
x² =2, (3)
2,(3)=(23-2)/9=21/9=7/3
x²=7/3
x=+/- √7/√3
(3x + 1)² - 20=101
(3x + 1)²=121
3x+1=11
x=10/3
3x+1=-11
x=-4
x²=9
x=+/- 3
7x²=64/7
x²=64/49
x=+/- 8/7
x² =2, (3)
2,(3)=(23-2)/9=21/9=7/3
x²=7/3
x=+/- √7/√3
(3x + 1)² - 20=101
(3x + 1)²=121
3x+1=11
x=10/3
3x+1=-11
x=-4
3x²=27
x²=27/3
x²=9
x₁=√9=3
x₂=-√9=-3
7x²=64/7
7·7x²=64
49x²=64
x²=64/49
x₁=√64/49=8/7
x₂=-8/7
x²=2,(3)
x²=(23-2)/9
x²=21/9=simplif cu 3=7/3
x₁=√7/√3=√21/3
x₂=-√21/3
(3x+1)²-20=101
9x²+6x+1-20=101
9x²+6x-19-101=0
9x²+6x-120=0 :3
3x²+2x-40=0
Δ=4+480=484
x₁=(-2+√484)/6=(-2+22)/6=20/6=10/3
x₂=(-2-22)/6=-24/6=-4
x²=27/3
x²=9
x₁=√9=3
x₂=-√9=-3
7x²=64/7
7·7x²=64
49x²=64
x²=64/49
x₁=√64/49=8/7
x₂=-8/7
x²=2,(3)
x²=(23-2)/9
x²=21/9=simplif cu 3=7/3
x₁=√7/√3=√21/3
x₂=-√21/3
(3x+1)²-20=101
9x²+6x+1-20=101
9x²+6x-19-101=0
9x²+6x-120=0 :3
3x²+2x-40=0
Δ=4+480=484
x₁=(-2+√484)/6=(-2+22)/6=20/6=10/3
x₂=(-2-22)/6=-24/6=-4